Türkı̇ye’de sı̇vı̇l toplum kuruluşları bağlamında örgün dı̇n eğı̇tı̇mı̇ tartışmaları: Din kültürü ve ahlak bilgisi dersi örneği - Sümeyra ARICAN (Türkiye Din Eğitimi Araştırmaları Dergisi)
Authoritarian structure of state-centred Turkey’s educational system increasingly faces demands and objections. By presenting the demands of the communities they represent in an institutional way, civil society organisations are located as political pressure elements. One of the constituents of formal religious education in Turkey, Religious and Moral Education, as a school subject, is quite rich in terms of demands and objections. Civil society organisations are determined to have been in the discussion platforms since the 1990s with an increasing effect. This study aims to reveal how civil society organisations, whose relations with religious education have changed, transformed and developed with professionalisation, approach and affect Religious and Moral Education and religious education policies with reference to their own publications. The study is designed as a multiple case study, in which qualitative data obtained via document analysis of twenty-eight civil society organisations that are selected through a maximum variation sampling method was analysed with a descriptive analysis method. Within the context of Religious and Moral Education, main findings of the study are evaluated in five different categories: ‘the status of the subject’, ‘secularism’, ‘education and religious education policies’, ‘exemption’ and ‘educational constituents’.